Glucose regulates steady-state levels of PDX1 via the reciprocal actions of GSK3 and AKT kinases - Humphrey, Rohan K. (2010)
The pancreatic beta cell is sensitive to even small changes in PDX1 protein levels; consequently, Pdx1 haploinsufficiency can inhibit beta cell growth and decrease insulin biosynthesis and gene expression, leading to compromised glucose-stimulated insulin secretion. Using metabolic labeling of primary islets and a cultured β cell line, we show that glucose levels modulate PDX1protein phosphorylation at a novel C-terminal GSK3 consensus that maps to serines 268 and 272. A decrease in glucose levels triggers increased turnover of the PDX1 protein in a GSK3-dependent manner, such that PDX1 phosphomutants are refractory to the destabilizing effect of low glucose. Glucose-stimulated activation of AKT and inhibition of GSK3 decrease PDX1 phosphorylation and delay degradation. Furthermore, direct pharmacologic inhibition of AKT destabilizes, and inhibition of GSK3 increasesPDX1proteinstability.These studies define a novel functional role for the PDX1 C terminus in mediating the effects of glucose and demonstrate that glucose modulates PDX1 stability via the AKT-GSK3 axis.